COUNTERCULTURE IN THE CONTEXT OF THE PROBLEM OF SOCIAL RESPONSIBILITY OF MAN TO NATURE - Mershchii, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The counterculture has become the quintessence of the modern youth-student movement, absorbing many characteristic contradictions of cultural and civilizational development in the era of modernization. The aim of the study is to analyze the content of the phenomenon of counterculture in connection with the attitude of its members to nature. This also involves considering counterculture as a historical but also a universal phenomenon, its understanding in line with the historical dynamics of the civilization process. Research methodology. Cultural-historical, socio-cultural, and synergetic approaches are used. The cultural-historical approach allows tracin the gradual development of counterculture on the example of mass youth-student movements in the leading Western countries of the second half of the XX century. The socio-cultural approach is applied to understand the problem of the attitude of counterculture to nature, determined by the needs and nature of society. The synergetic approach, on the contrary, is used to study counterculture in the historical dynamics of civilization in the form of cultural and countercultural dialectics. Research results. The 1960s were a time of the domination of some basic romantic ideas. The idea of free self-disclosure of the individual in his daily existence found a special sound. Among the counterculture initiatives, the project of "environmental socialism" of the 1980-s should be noted. The "green" movement was formed in the XX century. The meaning of "eco-socialism" lies in the reform of the world community, in which all issues of power and property are dependent on the task of eliminating antagonisms between society and nature. At the present stage of the development of civilization, the mass spread of the youth movement of counterculture and its popularity among various social strata of Western society absorbs certain phenomena of socio-cultural life, from subculture to mass culture in general. Discussion. Philosophical analysis of the intentions of the youth movement of counterculture indicates that global problems caused by man-made modernization of society force modern humanity to pay attention to local values, to seek and emphasize universal values in the form of a global worldview. Conclusions. Counterculture as a phenomenon can be considered in concrete-historical and universal aspects. As a concrete-historical phenomenon, counterculture is a complex of youth subcultures that unfolded from the second half of the XX century in leading Western countries, and then throughout the civilized world (including Ukraine), expressing the features of youth socialization in technogenic modernization of society and global problems of today. Analysis of the meaningful intentions of the counterculture movement allows, on the one hand, to consider it as a value-based project of co-evolutionary (ecological) modernization of a developed industrial society and modern man-made civilization. On the other hand, is to present it as a universal phenomenon that stimulates the further course of the cultural and civilizational process.